Innovating Brand Image: Mediating The Impact of Social Media Advertising Content and Social Media Sales Promotion Content on Behavioral Intentions for Clothing Distros in Bandar Lampung (A Study on Otsky Store Distro Products, Lampung) - Tinezia Sri Cendani; Mahrinasari MS; Mudji Rachmat Ramelan (International Journal of Regional Innovation, 2023)
The development of the business sector in MSMEs in the fashion sector has become widespread in society. The Otsky Store is one of the MSMEs in the fashion sector which is famous for its good quality t-shirts on the market. This study will analyze the effect of the influence of social media advertising and social media sales promotion content with brand image as a mediating variable on behavioral intention for Clothing Distro Otsky Store. By doing branding on social media platforms which are very influential due to using a content. Brand Image is needed as a mediating role in this research. This research is to test the positive and significant values of the variables. The method in this research uses quantitative descriptive. In this study using descriptive analysis that measures dominant indicators and weak indicators to draw conclusions and provide advice on the object being examined using PLS. The results of this research produced 121 respondents, the hypothesis value and the role of mediation were accepted with a p value <0.05 so the value was positive and significant for the variable. The mediation results revealed the significant role of brand image in explaining the relationship between social media advertising content, social media sales promotion content and behavioural intention.